Time Analysis of Muscle Activation during Basketball Free Throws - Paweł Pakosz; Mariusz Konieczny (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
Objective of the study: The study assessed and compared the duration of the muscle activation in a basketball free throw, by players representing a preliminary and specialist stage of training. There was also analysed the accuracy of throws according to the stage of training, and whether individual changes in duration of activation have impact on the accuracy of free throws. Material and methods: Players from national basketball teams second and third league of the AZS Academic Sports Club of Opole University performed twenty free throws shooting to the basket during the research study. During tests, players were equipped with EMG apparatus, which registered the time of muscle activation, when subsequent free throws were performed. Arm muscle (biceps and triceps) activation time was measured from the beginning of muscle activation to the time of completion of their work, and from muscle activation to the time of reaching the rim.Results: Players of specialist stage of training, have 0,30 sec shorter average arm muscle time activation, counted from the beginning of activation to obtain the minimum value, from players of the preliminary stage of training. They also gained average 2 points better result in throw accuracy. Variability coefficient of throws duration was higher by 19.56% at players of the specialist stage of training. In the case of unforced extend duration of muscle activation, 80% of specialists and 40% players of preliminary group, don’t score the basket.Conclusions: It was observed that the basketball players of higher training experience, have lower average time of arm muscle activation. It was demonstrated that in players of the specialist stage of training, missed free throws were mostly caused by longer duration from the beginning of muscle activity to the rim, with players of the preliminary stage it was reverse.